FRI0207 Induction of sustained remission in early inflammatory arthritis with the combination of infliximab plus methotrexate, methotrexate alone or placebo: the dinora trial. (15th June 2017) - Stamm, TA; Machold, K; Aletaha, D; Alasti, F; Lipsky, P; Pisetsky, D; Landewe, R; Heijde, D van der; Sepriano, A; Aringer, M; Boumpas, D; Burmester, G; et al.
Abstract : Background: Rheumatoid arthritis is a chronic form of inflammatory arthritis that is thought to have an early stage or reversibility with effective therapy ("window of opportunity"). Objectives: In the present study, we explored the effects of induction therapy with anti-TNFα antibody infliximab (IFX) plus methotrexate (MTX) compared with MTX alone and with placebo (PL) in patients with very early inflammatory arthritis. Methods: In an investigator-initiated, double-blind, randomized, placebo-controlled, multi-center trial, patients with synovitis of 12–16 weeks duration in at least 2 joints underwent one year of treatment with IFX in combination with MTX, MTX monotherapy or PL randomized in a 2:2:1 ratio. The primary endpoint was clinical remission after 1 year (sustained for at least two consecutive visits 8 weeks apart including week 54) with remission defined as no swollen joints, 0 - 2 tender joints and a C-reactive protein (CRP) level within the normal range (<0.5 mg/dl) or a normal ESR (<25 mm/h). Further, sustainability of remission was assessed during the second year of the study, during which patients received no treatment. The trial was registered at www.isrctn.com (ISRCTN21272423 ). Results: See Table 1 . 90 patients participated in the present study. At week 54 (primary endpoint), 32% of the patients in the IFX+MTX group achieved sustained remission compared with 14% on MTX alone and 0% on PL (Table). This difference was statistically significant for all three groups (p<0.05) and for IFX+MTX vs PL (p<0.05) separately, but not for IFX+MTX vs MTX (p=0.10), nor for MTX vs PL (p=0.31). Remission was maintained during the second year on no therapy in 75% of the IFX+MTX patients but was lost in 80% of the MTX-only-patients (Table). The analysis of radiographic progression did not reveal significant differences between the three treatment groups. The number needed to treat (NNT) to achieve one additional sustained remission at 52 weeks with IFX+MTX was 3 compared to placebo; the NNT for MTX alone versus placebo was 7 (NNT=6 for IFX+MTX vs MTX alone). Conclusions: These results indicate that patients with early arthritis can benefit from induction therapy with anti-TNF plus MTX compared to MTX alone, suggesting the existence of a window of opportunity where intensive treatment can alter the disease evolution Disclosure of Interest: T. Stamm Grant/research support from: For all authors: DINORA was partly funded by a grant from Janssen (previously Centocor). TS: AbbVie, Consultant for: AbbVie, Novartis, Speakers bureau: AbbVie, Janssen, MSD, Novartis and Roche, K. Machold: None declared, D. Aletaha Grant/research support from: AbbVie, Pfizer, Grünenthal, Merck Medac, UCB, Mitsubishi/Tanabe, Janssen and Roche, Consultant for: AbbVie, Pfizer, Grünenthal, Merck Medac, UCB, Mitsubishi/Tanabe, Janssen and Roche, F. Alasti: None declared, P. Lipsky Consultant for: Janssen, EMD Serono, Astra Zeneca, UCB, Roche, Celgene, Sanofi and Horizon, but none of them relates to the content of this manuscript, D. Pisetsky: None declared, R. Landewe Grant/research support from: Abbott, Amgen, Centocor, Novartis, Pfizer, Roche, Schering-Plough, UCB and Wyeth, Consultant for: Abbott/AbbVie, Ablynx, Amgen, Astra-Zeneca, Bristol Myers Squibb, Celgene, Janssen (formerly Centocor), Galapagos, Glaxo-Smith-Kline, Novartis, Novo-Nordisk, Merck, Pfizer, Roche, Schering-Plough, TiGenix, UCB and Wyeth, Employee of: RL is director of Rheumatology Consultancy BV which is a registered company under Dutch law., Speakers bureau: Abbott/AbbVie, Amgen, Bristol Myers Squibb, Janssen (formerly Centocor), Merck, Pfizer, Roche, Schering-Plough, UCB and Wyeth, D. van der Heijde Consultant for: AbbVie, Amgen, Astellas, AstraZeneca, BMS, Boeringer Ingelheim, Celgene, Daiichi, Eli-Lilly, Galapagos, Gilead, Janssen, Merck, Novartis, Pfizer, Regeneron, Roche, Sanofi and UCB, Employee of: DH is director of Imaging Rheumatology bv., A. Sepriano: None declared, M. Aringer Grant/research support from: MA's institution is clinical trial site for AbbVie, Astra Zeneca, Boehringer Ingelheim, Novartis, Pfizer and Roche., Consultant for: AbbVie, Astra Zeneca, BMS, Chugai, GSK, Hexal, Lilly, MSD, Novartis, Pfizer, Roche, Sanofi and UCB, Speakers bureau: AbbVie, Astra Zeneca, BMS, Chugai, GSK, Hexal, Lilly, MSD, Novartis, Pfizer, Roche, Sanofi and UCB, D. Boumpas: None declared, G. Burmester Grant/research support from: AbbVie, BMS, UCB and Roche, Speakers bureau: MSD, UCB and Roche, M. Cutolo Grant/research support from: BMS, Horizon, Actelion, Celgene and MSD, Speakers bureau: Biogen, Mundipharm, Pfizer and Menarini, W. Ebener Consultant for: Novartis and Abbvie, W. Graninger: None declared, T. Huizinga Consultant for: Merck, UCB, Bristol Myers Squibb, Biotest AG, Pfizer, GSK, Novartis, Roche, Sanofi-Aventis, Abbott, Crescendo Bioscience, Nycomed, Boeringher, Takeda, Epirus and Eli Lilly, G. Schett Speakers bureau: BMS, Celgene, Chugai, Lilly, Roche and UCB, H. Schulze-Koops Speakers bureau: AbbVie, Actelion, AstraZeneca, Biogen International, Boehringer Ingelheim, BMS, Celgene, Celltrion, Chugai, Cinfa Biotech, GSK, Hospira, Janssen-Cilag, Lilly, MSD, Medac, Merck, Mundipharma, Novartis, Pfizer, Hexal Sandoz, Roche and UCB, P. P. Tak Employee of: PPT has become an employee of GlaxoSmithKline. GSK has not been involved in this study., F. Breedveld: None declared, J. Smolen Grant/research support from: Abbvie, Lilly, MSD, Pfizer and Roche, Consultant for: Abbvie, Amgen, Astra-Zeneca, Astro, BMS, Boehringer-Ingelheim, Celgene, Celltrion, Chugai, Gilead, Glaxo, ILTOO, Janssen, Lilly, Medimmune, MSD, Novartis-Sandoz, Pfizer, Roche, Samsung, Sanofi and UCB